Pengaruh Penerapan Model Pembelajaran Inkuiri Terbimbing Pada Konsep Gerak dan Gaya Terhadap Kemampuan Bernalar Kritis Siswa Kelas VII SMP - Brenda Fajri Gibran; Sjaifuddin Sjaifuddin; Dwi Indah Suryani (PendIPA Journal of Science Education, 2026)
This study is based on field observation results showing that junior high school (SMP) teachers are not yet used to applying inquiry-based learning in the classroom with their students. A learning model is needed that can help achieve the learning goals in the Kurikulum Merdeka, one of which is the critical thingking dimension. Critical thinking is still a new aspect in teaching and learning activities, and the material on motion and force that involves students can be found and studied in everyday life. This study aims to find out the application of guided inquiry learning models on the critical thinking abilities of seventh-grade junior high school students on the concepts of motion and force. This study uses a quantitative method with a quasi-experimental type of non-equivalent control group design. The population in this study involved seventh-grade junior high school students with a sample of 30 students in the control and experimental classes. The data collection technique used tests. The research results show that the guided inquiry learning model affects the critical reasoning skills of seventh-grade junior high school students, proven by the sig.0.00 (two-tailed) < 0.05 results.